The Effectiveness of Budget Simulation Training in Improving Budget Preparation and Control Capabilities in MSMEs: The Role of Management Accounting Mediation - Henny Andriyani Wirananda; Sri Fitria Jayusman; Wilda Sri Munawaroh Harahap; Wan Dian Safina (FOUNDAE (Foundation of Advanced Education), 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in economic development; however, many experience high failure rates due to weak financial management capabilities, particularly in budgeting and financial control. Limited understanding of systematic budgeting and the lack of practical financial training often prevent MSME actors from effectively planning and monitoring their financial resources. Strengthening budgeting competencies through structured training interventions is therefore essential to improve the financial sustainability of MSMEs. This study aims to examine the effectiveness of budget simulation training in improving budget preparation and control capabilities among MSME actors, while considering the mediating role of management accounting practices. This study employed a quantitative approach using a one-group pretest–posttest quasi-experimental design. The sample consisted of 112 MSME actors selected through purposive sampling. Data were collected using questionnaires administered twice, namely before the training and four weeks after the intervention. Data analysis was conducted using paired sample t-tests and Partial Least Squares Structural Equation Modelling (PLS-SEM) with SmartPLS 4.0. The results show that budget simulation training has a positive and significant effect on budgeting skills (β = 0.347) and management accounting practices (β = 0.642). Management accounting practices also significantly influence budgeting skills (β = 0.468). Furthermore, management accounting practices partially mediate the relationship between training and budgeting skills, with a variance accounted for of 46.4%. These findings suggest that MSME capacity-building programs should integrate simulation-based budgeting training with guidance on the implementation of management accounting systems. This study contributes by integrating Experiential Learning Theory, Contingency Theory, and the Resource-Based View into a unified framework and empirically testing the mediating role of management accounting practices in MSME budgeting training in Indonesia.